Figurative Language Used in Mariah Carey’S Song Lyrics in Butterfly Album - Audrey Valeri; I Nyoman Sedeng; I Nyoman Udayana (CV. Ulil Albab Corp, 2023)
This undergraduate thesis entitled “Figurative Language Used in Mariah Carey’s Butterfly Album” is appealing to be discussed since figurative language is a relevant topic to the consistency of being used in literary work and song is an applicable object to be analyzed. This undergraduate thesis aimed to identify the types of figurative language and to explain the meaning of figurative language implied in Butterfly Album by Mariah Carey. The data of this thesis were taken from the album named Butterfly by Mariah Carey. The documentation method alongside with note-taking technique was used in this undergraduate thesis to collect the data. The qualitative method was used in this undergraduate thesis to analyze the data that has been collected. The data that have been analyzed were presented in the informal method alongside the descriptive technique. This undergraduate thesis used the theory stated by Knickerbocker and Reninger in the book Interpreting Literature (1963) and Leech in the book entitled Semantics: The Study of Meaning (1981) This undergraduate thesis identified types of figurative language in The Butterfly Album by Mariah Carey, those are simile, metaphor, synecdoche, metonymy, hyperbole, irony, and paradox. Furthermore, the types of meaning found in the album are conceptual, connotative, and affective.